The Effects of Exercise on Stress Levels - Srivastava, Sarthak (Journal of Educational Research and Policies, 2025)
According to WHO stress can be defined as a state of worry or mental tension caused by a difficult situation. Stress is a natural human response that prompts us to address challenges and threats in our lives. Everyone experiences stress to some degree. The way we respond to stress, however, makes a big difference to our overall wellbeing. But weather exercise is useful for relaxation from stress remains unclear. Therefore, the researchers intend to investigate to know the weather there was any significant effect of exercise on stress or not.46 girls' students of B. P. Ed. and another 23 girls' students of department of geography of Seva Bharati Mahavidyalaya for experimental and control group respectively mean age ranged from (21+2) years were selected for this study. Result showed that after 24 weeks 6.25% decrease in stress level of experimental group whereas, 3.03% increase in control group. This may be due to the body's compensation mechanisms have succeeded in overcoming the stressor's effect.